(untitled) (REMUNOM, 2026)
Antibiotics and corticosteroids are among the most frequently prescribed medications in pediatric populations and are widely used in the treatment of infectious and inflammatory conditions. However, inappropriate use of these pharmacological classes is associated with significant adverse outcomes, including antimicrobial resistance, immunosuppression, and increased healthcare costs. Despite the availability of clinical guidelines, substantial variability persists in prescribing practices, particularly regarding empirical use and adherence to institutional protocols. This study aimed to evaluate prescribing patterns and the degree of rational use of antibiotics and corticosteroids in children, identifying appropriate and inappropriate practices reported in recent literature. This systematic review was registered in PROSPERO (CRD420251045497) and conducted in accordance with PRISMA guidelines. Searches were performed in the SciELO, PubMed, and Virtual Health Library (VHL) databases, including studies published between 2019 and 2025, available in English and in full text. Clinical trials and observational studies addressing prescribing patterns and rational drug use in pediatrics were included. Thirteen studies met the eligibility criteria. A high prevalence of empirical antimicrobial prescribing was observed, with frequent use of broad-spectrum antibiotics and variable adherence to clinical guidelines. Regarding corticosteroids, benefits were limited to specific clinical conditions, and indiscriminate use was not supported by evidence. Persistent challenges in therapeutic rationality were identified, highlighting the need to strengthen antimicrobial stewardship programs, clinical protocols, and continuous educational strategies to promote safe and evidence-based prescribing practices in pediatric care.